Enhancing food security in an era of global climate change - Clark, W.C.; Kristjanson, Patricia M.; Campbell, Bruce M.; Juma, C.; Holbrook, N.M.; Nelson, Gerald C.; Dickson, N. (Center for International Development, Harvard University, 2010)
The goal of the workshop was to build a more strategic and integrated perspective on the threats and opportunities latent in the food / climate issue, and to discuss the hard challenges of moving forward toward common goals in a private, off-the-record setting. An executive session convened by the John F. Kennedy School of Government at Harvard University and the Venice International University on June 6-9, 2010 attracted more than 25 of the world’s leading experts from the fields of policy, science, and business to San Servolo Island for an intensive three day session (see text for a list of the participants). The discussions were off-the-record, with each participant present in his or her own capacity, rather than representing an organization. The session was one in a series on Grand Challenges of the Sustainability Transition organized by the Sustainability Science Program at Harvard University with the generous support of the Italy’s Ministry for Environment, Land and Sea. This particular session was held in cooperation with the new Mega Program on Climate Change, Agriculture and Food Security being developed by the Consultative Group on International Agricultural Research (CGIAR) and the Earth System Science Partnership. This summary report of the session is our synthesis of the main points and arguments that emerged from the discussions. It does not represent a consensus document, since no effort was made at the Session to arrive at a single consensus view. Rather, we report here on what we heard to be the major themes discussed at the session. Any errors or misrepresentations remain solely our responsibility.